An integrative study of Callicarpa gracilis Fewkes, 1881 and Aglaophenia trifida L. Agassiz, 1862, with notes on some hydroids (Cnidaria: Hydrozoa) from French Guiana - Galea, Horia R.; Di Camillo, Cristina G.; Maggioni, Davide (Zootaxa, 2021)
Among the thecate hydroids brought back by the Proteus-Guyane 2017 expedition of the Muséum national d’histoire naturelle of Paris, France, from French Guiana, two interesting species are reported upon. The plumulariid Callicarpa gracilis Fewkes, 1881, known so far from the type specimen only, is comprehensively redescribed 140 years after its original description. It adopts two different morphotypes with respect to both its tropho- and gonosome, forming either simple or ramified colonies, with either structurally-complex or rudimentary phylactocarps, respectively. Taxonomic notes on the genera Callicarpa Fewkes, 1881 and Hippurella Allman, 1877 are provided in light of their intricate history of origin and fate, together with the provisional resurrection of Antomma Stechow, 1919, as an allied genus of the former. The aglaopheniid Aglaophenia trifida L. Agassiz, 1862, whose gonosome was only partly documented to date, is redescribed thoroughly based on specimens bearing male and female corbulae. Scanning electron microscopy and molecular data were also used to document both species. A checklist of the thecate hydroids from French Guiana gathered during Proteus-Guyane 2017 and Guyane 2014 expeditions is provided as an appendix, together with brief notes on some species. Not dealing with the present study, but taking advantage of it, a new name, Antennella billardi Galea, nom. nov., is proposed as a replacement name for Plumularia balei Billard, 1911, which is a permanently invalid junior primary homonym of P. balei Bartlett, 1907.